MiRNAs dysregulated in association with Gleason grade regulate extracellular matrix, cytoskeleton and androgen receptor pathways. Issue 2 (24th July 2015) - Lichner, Zsuzsanna; Ding, Qiang; Samaan, Sara; Saleh, Carol; Nasser, Aurfan; Al‐Haddad, Sahar; Samuel, Joseph N; Fleshner, Neil E; Stephan, Carsten; Jung, Klaus; Yousef, George M
Abstract The Gleason grading system is an important determinant of treatment decisions and prognosis in prostate cancer. It has a number of limitations, including significant inter‐observer variability, creating a need for biological parameters to accurately assess the Gleason grade. The objective of this study was to determine the molecular correlates of the different Gleason grades. Global miRNA expression was analysed in pure regions of each Gleason grade. Bioinformatics analysis was performed to predict miRNA‐mediated signalling. We experimentally validated the effect of miRNAs on target gene expression and cellular functions using cell line models. We also examined the correlation of miRNAs with biochemical failure, metastasis and prognosis. We identified miRNAs that are differentially expressed between grades 3 and 5, and the top biological processes associated with Gleason grade transition were extracellular matrix (ECM)‐mediated signalling, focal adhesion kinase‐ and mitogen‐activated kinase pathways. Transfection with miR‐29c, miR‐34a and miR‐141 repressed genes involved in ECM‐mediated pathways, such as SRC, PRKCA, COL1A1, ITGB1 and MAPK13, and decreased cell proliferation and migration. Furthermore, miR‐29c and miR‐34a influenced downstream pathways that affect actin cytoskeleton organization and androgen receptor localization. Finally, miR‐29c, miR‐34a, miR‐141 and miR‐148a showed inverse correlations with biochemical recurrence, but were independent of other clinical parameters. Our results demonstrate the potential role of miRNAs as independent prognostic markers and pave the road for a biological‐based reclassification of the Gleason grading system. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.